Research on sensitizing agent formulation for emulsion explosives using in open-cast - Lê Viết, Tú; Nguyen Trung, Toàn; Dam Quang, Sang (Journal of Military Science and Technology, 2024)
Emulsion explosives are low-sensitivity explosive materials that are often sensitized with gas-forming agents or glass microspheres to increase their reliable detonation ability. However, the above sensitization methods still have many limitations, such as low stability and high cost. In this study, emulsion explosives were sensitized with a new sensitive additive component, including NH4NO3, NaClO4, H2O, solution of NaNO2 15%, and solution of H3PO4 10%. The research results showed that adding about 30 ÷ 35% NH4NO3, 9 ÷ 10% NaClO4, and reducing up to 40% NaNO2 compared to emulsion explosives using only sensitive additive components including solution of NaNO2 15% and solution of H3PO4 10% not only ensured the technical requirements but also helped to limit the decrease in sensitivity and energy characteristics of emulsion explosives over time of storage.